Spatio-Temporal Drought Assessment Using Standardized Precipitation Evapotranspiration Index (SPEI) over Mantaro Valley, Peru - Arana Ruedas, Del Piero Raphael (2023)
Peru has several studies based on the Peruvian Tropical Andes (PTA) and its effects due to climate change. It has been shown that due to orography characteristics, different kinds of climate conditions are seen. In that sense, the PTA has a very complex climate system, which causes significant variability mostly related to an increase in temperature and a decrease in precipitation patterns. The Mantaro Valley is located in the PTA, Junin region. Where vulnerable farmers are already affected by poverty, practice agriculture based on rain-fed cropping systems. Hence, climate variability causes agricultural vulnerability and water resource scarcity. This study aims to elaborate the Spatio-temporal drought assessment over Mantaro Valley to provide information on local climate change events. In order to do so, the Standardized Precipitation Evapotranspiration Index (SPEI), recognized by the World Meteorological Organization (WMO), was used. The results have shown that almost every station has clear evidence of warming over the years and only a precipitation decrease in two out of six stations. Furthermore, the Spatio-temporal analysis shows around 30% of drought events from the total data, considering the frequency, severity, and duration. In conclusion, it has been demonstrated that all analyzed stations within Mantaro Valley have the same deportment regarding drought characteristics with different highest frequency per time scale. Finally, it is recommended to keep tracking stations with the lowest available data, realize comparison analysis with different drought assessment methods, and study the correlation between drought and ENSO events and other climate events such as floods.